REVIEW OF WORK ON MULTIPHASE FLOWS IN THE FORMATION AND WELL IN RELATION TO THE THERMOMETRY OF WELLS - Bobonazarov, Dilshod; Bekmirzaev , Rahmatillo; Mamatmuradova , Mohigul (Физико-технологического образование, 2022)
It is noted in this article that the underground layers are studied in the measurement of harnesses and pressures in multi-flow layers, and the data on the layer number. a lot of work is being carried out on this subject in the directions of physics and Geophysics in higher educational institutions